Facing contradictory emotions in event marketing: leveraging on surprise. Issue 2 (19th March 2018) - Addis, Michela; Miniero, Giulia; Soscia, Isabella
Abstract : Purpose: This paper aims to explore the role of surprise in reducing the negative impact of an undesired emotion, such as embarrassment, on the attitudes and behavioral intentions of consumers taking part in an event. Design/methodology/approach: In total, 220 consumers took part in a pre-test/post-test quasi-experimental within-subject design. Data were analyzed using structural equation modeling. Findings: Findings show that an in-store social event designed to elicit young customers' surprise and feelings of romantic love might also give rise to a relevant negative emotion such as embarrassment, and that surprise can act as a powerful managerial tool in limiting the negative effects of this negative emotion. Moreover, brand attitude and purchase intention are outcomes of positive emotions elicited by the event. Practical implications: The study shows that event marketing is an appealing but risky strategy. Evoking surprise is an effective way to manage negative emotions such as embarrassment that can arise unintentionally during an event. Originality/value: The research contributes to the understanding of the role of contradictory emotions in a specific social experience, namely, the event, and focuses on unplanned and undesired the affective contributions of customers.